Effects Of Dietary Rucah Fish Meal On The Digestive Organ Weight Of Native Chickens - Nurhayati; Imam Miftahudin; Nelwida; Lisna; Fauzan Ramadan; Filawati (INDONESIAN JOURNAL OF SMALL SCALE FARMING, 2026)
BACKGROUND AND OBJECTIVES Native chickens are local poultry with high economic value; however, their productivity remains relatively low, making nutritional improvement particularly from protein sources essential. Trash fish or discarded fish or rucah fish meal has potential as an alternative feed ingredient due to its abundant availability, lower cost, and high protein content. Its utilization may reduce production costs without compromising feed nutritional quality. This study aimed to evaluate the effect of rucah fish meal inclusion in the diet on the digestive organ weights of native chickens. METHODS The experiment was conducted at the Livestock and Forage Cultivation Laboratory, Faculty of Animal Science, Universitas Jambi, using 200 native chickens. A completely randomized design with five dietary treatments and four replications was applied. The treatments consisted of different inclusion levels of rucah fish meal: P0 = 12%, P1 = 14%, P2 = 16%, P3 = 18%, and P4 = 20%, with four replications per treatment. The observed parameters included feed intake, slaughter weight, relative weight of the gizzard, relative weight of the pancreas, and relative weight of the liver. Data were analyzed using analysis of variance (ANOVA), and parameters showing significant effects were further analyzed using Duncan’s multiple range test. FINDINGS The results indicated that the inclusion of rucah fish meal up to 20% in the diet had no significant effect on feed intake, slaughter weight, relative gizzard weight, relative pancreas weight, or relative liver weight of native chickens. CONCLUSION Rucah fish meal can be included in native chicken diets at levels of up to 20% without adversely affecting the performance of digestive organs as reflected by organ weights